Mendiskusikan Definisi Sastra Islam dan Sastra Islami dalam Kesusastraan Indonesia Masa Kini - Dian Rizky Azhari; M. Yoesoef; Turita Indah Setyani (Universitas Mulawarman, 2022)
The use of the terminology of Islam Literature and Islamic Literature by literary academics and readers in Indonesia is still confusing. It is inseparable from the development of Islam in Indonesia after the New Order. At that time, publishers had a unilateral claim that their work was the work of Islam literature or Islamic literature. Based on that, this study aims to find the definition and characteristics of the terminology of Islam Literature and Islamic Literature. This study uses the dialectical method, which is a method that contrasts several different views on a problem, in this case, the definition of Islam Literature and Islamic Literature. To collect data, this study uses a literature study of experts' opinions, literary observers, data on literary works, and the development of Indonesian literature. The results of the discussion show that Islam literature refers to all literary works that are strictly based on the text of the holy book and hadith; while Islamic literature can be more fluid than Islamic literature, it does not have to be based on scriptures and hadith, but the values ​​contained in it must be still based on Islamic teachings.